Video Captions for Online Courses: Do YouTube's Auto-generated Captions Meet Deaf Students' Needs? - Becky Sue Parton (Flexible Learning Association of New Zealand, 2016)
Providing captions for videos used in online courses is an area of interest for institutions of higher education. There are legal and ethical ramifications as well as time constraints to consider. Captioning tools are available, but some universities rely on the auto-generated YouTube captions. This study looked at a particular type of video-the weekly informal news update created by individual professors for their online classes-to see if automatic captions (also known as subtitles) are sufficiently accurate to meet the needs of deaf students. A total of 68 minutes of video captions were analysed and 525 phrase-level errors were found. On average, therefore, there were 7.7 phrase errors per minute. Findings indicate that auto-generated captions are too inaccurate to be used exclusively. Additional studies are needed to determine whether they can provide a starting point for a process of captioning that reduces the preparation time.